The Vicious Cycle: Problematic Family Relations, Substance Abuse, and Crime in Adolescence: A Narrative Review - Saladino, Valeria; Mosca, Oriana; Petruccelli, Filippo; Hoelzlhammer, Lilli; Lauriola, Marco; Verrastro, Valeria; Cabras, Cristina (Frontiers in Psychology, 2021)
Despite the copiousness of studies about the risky behaviors of adolescents, we cannot establish with certainty the leading aspects involved in teens' substance abuse and criminal actions. This review aims to explore the interplay among the family system, substance abuse, and criminal behavior. The analysis of the main results of 61 articles published between 2010 and 2020 shows that adolescents whose parents are justice-involved and often absent from home, are more likely to perceive lower cohesion, support, and poor communication in family. These factors can involve them in criminal acts and substance abuse. Moreover, these conducts are often linked to a form of uneasiness and a search of autonomy. Indeed, risky behaviors could have more than one meaning. Our findings suggest also that in adolescence the most diffused drug-related crimes are economic crimes, weapon carrying, robberies, dealing, and possession of drugs. Considering these results, future clinical implications might be based on multidimensional approaches, focusing more on family context, to promote interventions for at-risk adolescents.